Bradyrhizobium frederickii sp. nov., a nitrogen-fixing lineage isolated from nodules of the caesalpinioid species Chamaecrista fasciculata and characterized by tolerance to high temperature in vitro. Issue 12 (5th September 2019) - Urquiaga, Maria Clara de Oliveira; Klepa, Milena Serenato; Somasegaran, Padma; Ribeiro, Renan Augusto; Delamuta, Jakeline Renata Marcon; Hungria, Mariangela
Abstract : The symbioses between legumes and nitrogen-fixing rhizobia make the greatest contribution to the global nitrogen input via the process of biological nitrogen fixation (BNF). Bradyrhizobium stands out as the main genus nodulating basal Caesalpinioideae. We performed a polyphasic study with 11 strains isolated from root nodules of Chamaecristafasciculata, an annual multi-functional native legume of the USA. In the 16S rRNA gene phylogeny the strains were clustered in the Bradyrhizobium japonicum superclade. The results of analysis of the intergenic transcribed spacer (ITS) indicated less than 89.9 % similarity to other Bradyrhizobium species. Multilocus sequence analysis (MLSA) with four housekeeping genes ( glnII, gyrB, recA and rpoB ) confirmed the new group, sharing less than 95.2 % nucleotide identity with other species. The MLSA with 10 housekeeping genes ( atpD, dnaK, gap, glnII, gltA, gyrB, pnp, recA, rpoB and thrC ) indicated Bradyrhizobium daqingense as the closest species. Noteworthy, high genetic diversity among the strains was confirmed in the analyses of ITS, MLSA and BOX-PCR. Average nucleotide identity and digital DNA–DNA hybridization values were below the threshold of described Bradyrhizobium species, of 89.7 and 40 %, respectively. In the nifH and nodC phylogenies, the strains were grouped together, but with an indication of horizontal gene transfer, showing higher similarity to Bradyrhizobium arachidis and Bradyrhizobium forestalis . Other phenotypic, genotypic and symbiotic properties were evaluated, and the results altogether support the description of the CNPSo strains as representatives of the new species Bradyrhizobium frederickii sp. nov., with CNPSo 3426 T (=USDA 10052 T =U686 T =CL 20 T ) as the type strain.